A JOURNEY ACROSS THE ATLANTIC: THE HISTORY OF MELODRAMA IN WESTERN LANDSCAPE - Basuki, Ribut (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
Melodrama has long been considered as a genre with no artistic value by theatre/drama historians. It is there to cater the tastes of the lower class or the popular society; thus, it is not a genre worthy of literary scholars. Through New Historicism lens, however, such a consideration is given by people with elitist point of view. As it is discussed in the following paper, melodrama has a lot to offer. It has been a genre with a lot of values attached to it since it's "birth" in France, its development in England, and maturation in the United States. Unlike the other genres, which are not free from values and biases, melodrama is more frank in delivering its messages.